Effect of 22(S), 23(S)-Homobrassinolide on Adventitious Root Formation in Grape Rootstocks - Kaplan, U.; Gökbayrak, Z. (South African Journal of Enology and Viticulture, 2016)
In recent times, brassinosteroids have been identified as a group of hormones that regulate plant growth and development. They affect plant development from seed germination to senescence. The aim of this research was to study the effects of brassinosteroids on the rooting of three American grapevine rootstocks (1103 Paulsen, 110 Richter and 99 Richter) used frequently to produce grafted grapevines. Rootstock cuttings were dipped for 10 minutes into five different concentrations of 22(S), 23(S)-homobrassinolide and planted into a peat-perlite mixture. Data such as fresh and dry root weight, root number and development level were collected and assessed. Some shoot growth features were also determined. The results showed that the grapevine rootstocks with the most significant response in improved root and shoot growth were 1103 Paulsen, followed by 110 Richter. Root development level was influenced by both the rootstock and the concentrations of the substance. The lowest concentration, 0.05 ppm, induced more root numbers in 1103 Paulsen, while 0.15 ppm resulted in the highest number of roots in 99 Richter. A statistical analysis of the data revealed a significant difference between root development and shoot growth.